Sistema de Gestão da Informação e a Tomada de Decisão: estudo de caso da Câmara Municipal de Sesimbra - Rodrigues, Fernanda (2008)
Sistema de Gestão da Informação e a Tomada de Decisão: estudo de caso da Câmara Municipal de Sesimbra